2023
DOI: 10.1002/anie.202302286
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light‐Driven Conversion of Carbon‐Sequestrated Seawater into Stoichiometric CO and HClO with Nitrogen‐Doped BiOCl Atomic Layers

Abstract: Seawater is one of the most important CO2 sequestration media for delivering value‐added chemicals/fuels and active chlorine; however, this scenario is plagued by sluggish reaction rates and poor product selectivity. Herein, we first report the synthesis of nitrogen‐doped BiOCl atomic layers to directly split carbon‐sequestrated natural seawater (Yellow Sea, China) into stoichiometric CO (92.8 μmol h−1) and HClO (83.2 μmol h−1) under visible light with selectivities greater than 90 %. Photoelectrons enriched o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…Anion vacancies are the widely studied defects in photocatalysis, such as O vacancy, C vacancy, and S vacancy. , In many systems, these point defects, especially the O vacancies, can be spontaneously created owing to the relatively low vaporization enthalpy. For example, our group engineered O vacancies into Bi 12 O 17 Cl 2 and Bi 2 Sn 2 O 7 via a facile solvothermal process (Figure a). , Based on the absorption of microwave radiation by an unpaired electron and transitions between quantized states of the resulting magnetic moment, the O vacancies can be well identified through electron paramagnetic resonance (EPR).…”
Section: Types Of Defects In 2d Atomic Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Anion vacancies are the widely studied defects in photocatalysis, such as O vacancy, C vacancy, and S vacancy. , In many systems, these point defects, especially the O vacancies, can be spontaneously created owing to the relatively low vaporization enthalpy. For example, our group engineered O vacancies into Bi 12 O 17 Cl 2 and Bi 2 Sn 2 O 7 via a facile solvothermal process (Figure a). , Based on the absorption of microwave radiation by an unpaired electron and transitions between quantized states of the resulting magnetic moment, the O vacancies can be well identified through electron paramagnetic resonance (EPR).…”
Section: Types Of Defects In 2d Atomic Layersmentioning
confidence: 99%
“…Anion vacancies are the widely studied defects in photocatalysis, such as O vacancy, C vacancy, and S vacancy. 25,26 In many systems, these point defects, especially the O vacancies, can be spontaneously created owing to the relatively low vaporization enthalpy. For example, our group engineered O vacancies into Bi 12 O 17 Cl 2 and Bi 2 Sn 2 O 7 via a facile solvothermal process (Figure 2a).…”
Section: Anion Vacanciesmentioning
confidence: 99%
“…27 Most recent studies have suggested that Vo can further improve catalytic performance. 28–30 Vo can improve the performance of LSBs by tuning their electronic structure and regulating their intrinsic physiochemical properties; meanwhile, they are considered the sites of adsorption and catalysis for the immobilization and conversion of LiPSs during SRRs and SORs. 31–34 Unfortunately, Vo are seen as a double-edged sword whose instability tends to cause a decrease in catalytic performance during cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Photoreduction of CO 2 to valuable chemicals holds great promise for alleviating global warming and the energy crisis. Among various nanomaterials, TiO 2 has been widely investigated for photocatalytic CO 2 conversion due to the low cost, high chemical stability, and suitable redox potential for CO 2 reduction. However, the unfavorable band gap (3.2 eV) and sluggish interfacial charge transfer limit its performance within the visible light region. , To date, many approaches have been developed to settle these issues, such as doping, , defect engineering, , and heterogeneous structure design. Although increasing the photocatalytic yield is a primary focus, the issue of product selectivity is often overlooked. Therefore, designing a TiO 2 -based nanostructure that can effectively boost both the yield and selectivity of CO 2 photoreduction still remains a challenge.…”
Section: Introductionmentioning
confidence: 99%